Conflict Management in Organizations: Historical, Theoretical, and Strategic Approaches - Lusiana, Nanda; Utarindasari, Destiana (International Journal of Sharia Business Management, 2025)
Conflict within organizations is an inevitable phenomenon that often arises due to differences in interests, perceptions, or goals among individuals and departments. This study aims to comprehensively examine conflict management, including its history, definitions, causal factors, functions, and resolution strategies. Using a descriptive qualitative approach through literature review, data were collected from various credible and relevant scientific sources, both printed and digital. The findings indicate that conflict management serves not only as a problem-solving mechanism but also as a strategic tool to enhance team cohesion and work effectiveness when managed properly. Constructively managed conflict can become a source of innovation and work motivation. This study also highlights that the effectiveness of conflict management is more influenced by individuals’ understanding of relational dynamics and how they frame conflict, rather than by personality or gender alone. The novelty of this research lies in its integrative approach, combining historical, theoretical, and practical perspectives, and it proposes the development of a training model based on framing and interpersonal relations as a strategic solution to address conflict challenges in modern organizational settings.